A quality improvement initiative to reduce excess inhaled therapy use in the neonatal intensive care unit - Zierk, Avery; Gumbel, Mary Jo; Mackenzie, Rachel; Matthews, Kelle; Simmons, Francis; Bustin, Anna; DeFelice, Christina; Morris, Heidi; Soorikian, Leane; Swartz, Kimberly; Nickel, Amanda; Gibbs, Kathleen (Journal of perinatology, 2024)
Inhaled medications are commonly used at our single-center, Level IV neonatal intensive care unit (NICU). We lacked a standardized process for measuring efficacy of these medications to guide optimal duration of use, potentially leading to their overuse. We utilized quality improvement methodology to reduce the length of inhaled hypertonic saline (HTS) course durations and high frequency albuterol use. Interventions included education, data sharing, and implementation of a respiratory therapy assessment tool. The average inhaled HTS course duration decreased from 8.7 to 4.2 days. The percentage of q4 albuterol administrations per total albuterol doses administered monthly decreased from 39 to 20%. Developing a shared mental model between interprofessional providers for the indication and effect of inhaled agents and standardizing assessment of these medications' efficacy can reduce their overuse.